The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1158/1078-0432.ccr-15-1356
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Resistance in Diffuse-Type Gastric Adenocarcinoma Is Mediated by RhoA Activation in Cancer Stem-Like Cells

Abstract: Purpose The Lauren diffuse type of gastric adenocarcinoma (DGA), as opposed to the intestinal type (IGA), often harbor mutations in RHOA but little is known about the role of RhoA in DGA. Experimental Design We examined RhoA activity and RhoA pathway inhibition in DGA cell lines and in two mouse xenograft models. RhoA activity was also assessed in patient tumor samples. Results RhoA activity was higher in DGA compared to IGA cell lines, and was further increased when grown as spheroids to enrich for cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 44 publications
5
91
0
Order By: Relevance
“…Cell adhesion– and RhO GTPase–related genes were enriched in diffuse GC, which could be interpreted by the high mutation and methylation level of CDH1 [10] and the high mutation rate of RhoA gene [30], [31]. Cell cycle and p53-DNA repair–related genes were found enriched in intestinal GC, which is in coincidence with previous reports [15], [32].…”
Section: Discussionsupporting
confidence: 86%
“…Cell adhesion– and RhO GTPase–related genes were enriched in diffuse GC, which could be interpreted by the high mutation and methylation level of CDH1 [10] and the high mutation rate of RhoA gene [30], [31]. Cell cycle and p53-DNA repair–related genes were found enriched in intestinal GC, which is in coincidence with previous reports [15], [32].…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with these results, the protein levels of SOX2 and NANOG, but not OCT4, were increased in SS#2 spheroids (Figure 3B). These data suggest that among those three genes, SOX2 and NANOG are the key factor conferring stemness characteristics in spheroid-forming ability as previous studies reported [19,20]. Furthermore, higher expression levels of those genes in SS#2 than TS#2 demonstrate that our novel method isolated more homogeneous spheroid cells with stem-like characteristics.…”
Section: Resultssupporting
confidence: 76%
“…5-fluorouracil was purchased from US Biological, and cisplatin was purchased from Enzo Life Sciences. Gastric cancer cell lines were grown as spheroids and spheroids were counted as previously described (14). …”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (14) using the following antibodies: Akt (sc-8312, Santa Cruz Biotechnology), ERK1 (sc-271270, Santa Cruz Biotechnology), p38 (sc-81621, Santa Cruz Biotechnology), JNK2 (sc-827, Santa Cruz Biotechnology), CD24 (sc-11406, Santa Cruz Biotechnology), c-Myc (sc-40, Santa Cruz Biotechnology), Sox2 (#2748, #3579), Oct-4 (#2750), Nanog (#4893), Slug (#9585), Snail (#3879), phospho-Akt (ser473) (#9271), phospho-p38 (#9211), phospho-ERK1/2 (#9101), phospho-JNK1/2 (#9251), CD44 (#3578), Musashi-1 (#2154),, cleaved caspase-3 (#9661), Rac1 (BD 61065, BD Biosciences), N-cadherin (BD 610920, BD Biosciences), Zeb1 (NBP-1-05987, Novus Biologicals), CD133 (MBS462020, MYBioSource), and β-actin (A5228, Sigma)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation